Embryo transfer in camelids: Study of a reliable superovulatory treatment in llamas - Huanca López, Wilfredo (2006)
South American Camelids are receiving increased interest not only in South America but also on a worldwide scale. They possess some unique features such as their fine fibre and their high adaptivity to many climatic regions across the world. Apart from the important productive aspects, their physical attractiveness also makes them popular as pet animals. However there are still many gaps in the scientific literature with regard to South American Camelids. This collection of papers brings experience of both South American and European experts together. It considers current trends in reproduction, nutrition, health, fibre morphology and genetics and discusses as new topic aspects of the potential of meat production and commercialization in South America. The particular advantages of South American Camelids for the sustainable use of fragile ecosystems with native pastures are outlined. Round tables discussions focus on the interaction between wild and domestic species, the management of alpaca populations outside of South America and health aspects under European conditions.